Hybrid Management of an Ulnar Artery Pseudoaneurysm Postphlebotomy - Moriarty, Heather K.; Charalabidis, Peter; Musicki, Korana; Phan, Tuan; Joseph, Tim; Clements, Warren (Journal of Clinical Interventional Radiology ISVIR, 2019)
The purpose of this case report is to describe the occurrence and management of an ulnar artery pseudoaneurysm post phlebotomy. A 36-year-old worker with progressively painful nondominant forearm swelling was referred at 4 weeks postphlebotomy. Serial imaging showed an expanding proximal ulnar pseudoaneurysm. This was managed with a covered stent in the ulnar artery and coiling of the interosseous artery. The hematoma was evacuated, and the neurovascular bundle was protected with muscle coverage. At follow-up, the stent was patent, and there was no distal ischemia. Pseudoaneurysms post phlebotomy are rare. We demonstrate successful treatment of an ulnar artery pseudoaneurysm with stent graft and coiling of the interosseous branch.
Keywords: pseudoaneurysm; ulnar artery; endovascular; stent graft; phlebotomy